A CONSTRUÇÃO DA IDENTIDADE HISTÓRICO-CULTURAL NO ESPAÇO ESCOLAR: UMA EXPERIÊNCIA DE TRABALHO COM A DANÇA AFRO NO ENSINO DE EDUCAÇÃO FÍSICA - Serafim, Lielle (2020)
Afro dance has been present for a long time in the history of Espírito Santo and São Mateus until nowadays, composing an important feature in the affirmation of the identity of the black population of the region. However, it is clear that affirmative acti